OPTIMALISASI PELAKSANAAN HAK INISIATIF DPRD TERHADAP PEMBENTUKAN PERATURAN DAERAH DI KABUPATEN WONOGIRI - Prihatini, Endah Retno; Firdausy, Adriana Grahani (Res Publica: Jurnal Hukum Kebijakan Publik, 2019)
Optimizing the role of DPRD is the work achieved by DPRD related with their authority and responsibility. The performance indicators of public organization are productivity, service quality, responsiveness, responsibility, and accountability. This research focuses on the functions of Regional Regulation (perda) Assembly. This study also aims to comprehend the implementation of initiative right from DPRD Wonogiri in assembling the regional regulation (perda). The method which is used in this judicial writing is juridical empiric. The result shows that DPRD Wonogiri in implementing the initiative right has been run well but not optimally conducted, it can be seen from the drafts of Regional Regulation (perda) from initiative right which are lesser than the amount of Regional Regulation (perda) drafts from Local Government. It happened due to the work bearer factors which are Executive tradition as Regional Regulation (perda) Refinement, many new members of DPRD, the characteristic of DPRD as democracy institution, and the replacement/extraction of reference regulation in assembling Regional Regulation (perda). The solutions that can be taken to maximize the initiative right of DPRD Wonogiri are by being more active in apprehending people’s aspirations, maximizing professional bintek, and increasing the information management for community.